2007
DOI: 10.1021/jf072792n
|View full text |Cite
|
Sign up to set email alerts
|

Dose Formulation and Analysis of Diapocynin

Abstract: Procedures based on high-performance liquid chromatography (HPLC) with ultraviolet (UV) detection and liquid chromatography-mass spectrometry (LC-MS) are described for analyzing diapocynin. Diapocynin was synthesized by oxidative coupling of two apocynin monomers, through the in situ generation of sulfate radicals. It was purified by washing 3 times each with boiling water, followed by boiling methanol. HPLC was used to determine the concentration of unreacted apocynin and other impurities and the purity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 13 publications
0
36
0
1
Order By: Relevance
“…Recent studies have shown conversion of apocynin to diapocynin (apocynin dimer) in vivo, which prevents the assembly and activation of the NADPH oxidase complex [13]. Additionally, diapocynin is 13-fold more lipophilic than apocynin [22]. Here, we show that diapocynin inhibits MPTP-induced activation and expression of both iNOS and gp91phox in activated glial cells, suggesting that diapocynin has anti-inflammatory properties against neurotoxic stress.…”
Section: Discussionmentioning
confidence: 54%
“…Recent studies have shown conversion of apocynin to diapocynin (apocynin dimer) in vivo, which prevents the assembly and activation of the NADPH oxidase complex [13]. Additionally, diapocynin is 13-fold more lipophilic than apocynin [22]. Here, we show that diapocynin inhibits MPTP-induced activation and expression of both iNOS and gp91phox in activated glial cells, suggesting that diapocynin has anti-inflammatory properties against neurotoxic stress.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, we have shown that diapocynin (apocynin dimer) reduced neuroinflammation and protected dopaminergic neurons in the MPTP mouse model of PD (Ghosh et al, 2012b) by preventing the assembly and activation of the NADPH oxidase complex. Diapocynin is 13-fold more lipophilic than the monomer apocynin (Luchtefeld et al, 2008). Later, we demonstrated that diapocynin successfully prevented motor deficits in the leucine-rich repeat kinase 2 (LRRK2 R1441G ) transgenic mouse (Dranka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…One such compound listed as NADPH oxidase inhibitor is apocyanin, (4-hydroxy-3-methoxyacetophenone), a plantderived antioxidant originally isolated from the medicinal plant Picrorhiza kurroa [16]. It is lipophyllic in nature and can easily cross cell membrane [17]. Being a selective inhibitor of NADPH oxidase, it can block the production of superoxide and oxygen free radicals that typically accompany inflammation.…”
Section: Introductionmentioning
confidence: 99%